Key to the species of Ptilomerinae (Hemiptera: Heteroptera: Gerridae) of Thailand and review of the fauna of the Tennaserim Mountain Range - Raruanysong, Sajeemat; Vitheepradit, Akekawat; Sites, Robert W. (Zootaxa, 2014)
Water striders of the subfamily Ptilomerinae (Hemiptera: Heteroptera: Gerridae) are commonly found in lotic habitats such as streams, rivers and waterfalls. Eight species representing four genera were recorded from the Tennaserim Mountain Range, including a new country record of Pleciobates tuberculatus Esaki from Thailand. This paper provides illustrations and ecological notes on Ptilomerinae in the Tennaserim Mountain Range in Thailand and a taxonomic key for identification of all species throughout Thailand.